Impact of lifestyle and mood on vestibular migraine and advancements in non-pharmacological treatments - DONG Xuanyu, YAO Xiaodong (Xin yixue)
Vestibular migraine is a hereditary disease characterized by recurrent vestibular symptoms， with a higher incidence in females than in males， and is often associated with poor lifestyle and mood， most commonly stress， sleep disorders， and anxiety and depression. Since there is no preferred pharmacological treatment， and the changes in lifestyle and improvement of mood are proving to be effective in controlling vestibular migraine symptoms， non-pharmacological treatments are becoming more important. Avoidance of triggering factors， lifestyles changes， vestibular rehabilitation， cognitive-behavioral therapy， and acupuncture are the main approaches of non-pharmacological treatment. This article mainly analyses the effects of lifestyle and mood on vestibular migraine， and discusses the progress of non-pharmacological treatment of vestibular migraine.